Variantes anatómicas asociadas a desviación del septum nasal identificadas por tomografía computarizada en una clínica privada de Lima 2018 - Lorena del Pilar, Córdova Sánchez (2020)
ABSTRACT Objetive: To describe the anatomical variants of the nasal turbinates and the thickening of the nasal mucous of paranasal sinuses identificate by simple computed tomography of the paranasal sinuses in patients with nasal septal deviation. Methodology: Observational, analytical, cross sectorial and retrospective research. The 227 cases of adult patients with nasal septal deformity were studied, classified according to Mladina and its anatomical variants identified by computed tomography during the year 2018 at the Clínica Internacional of Lima. Data were collection on a sheet tabulated and analyzed using Stata version 15 with a level of significance of 95%. Results: In the upper turbinates, 3% had pneumatization and about 18.5% were absent; in the middle, 70% preseted variations, the most frecuent variant being hypertrophy followed by concha bullosa and paradoxical with 30.84%; 14.98% and 7.89% respectively. In the inferior turbinates, 75.77% were hyperthophy, 64.3% presented thickening of the mucous of the paranasal sinuses. The association was stadistically significant between the presence of spur, alteration of the nasal valve with to the type of Mladina deformity and the vertical types were the most frecuent. Conclusion: Patients with nasal septal deformity have a higher frecuency of nasal valve alteration and mucous thickening of the paranasal sinuses. The most frecuency anatomical variants of middle turbinates are hypertrophy and concha bullosa, in the inferior are hypertrophy and the presence of spurs and alterations of the nasal valve are associate with type of Mladina deformity.